(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Education cannot be distinguished from two main factors; teacher and student. Without both of these two factors, it is not actually education. Education in Uzbekistan is still far from expected. This can be seen from the presence of difficulties in achieving decent labor results in accordance with the educational level of graduates. One of the reasons for the low quality of education in Uzbekistan is that the qualifications of teachers as teachers are still considered low compared to the standards prepared. This article discusses the impact of teacher competence on student competence, particularly in the study of mathematics.